Tissue factor in atherosclerosis and atherothrombosis. (August 2020) - Grover, Steven P.; Mackman, Nigel
Abstract: Atherosclerosis is a chronic inflammatory disease that is characterized by the formation of lipid rich plaques in the wall of medium to large sized arteries. Atherothrombosis represents the terminal manifestation of this pathology in which atherosclerotic plaque rupture or erosion triggers the formation of occlusive thrombi. Occlusion of arteries and resultant tissue ischemia in the heart and brain causes myocardial infarction and stroke, respectively. Tissue factor (TF) is the receptor for the coagulation protease factor VIIa, and formation of the TF:factor VIIa complex triggers blood coagulation. TF is expressed at high levels in atherosclerotic plaques by both macrophage-derived foam cells and vascular smooth muscle cells, as well as extracellular vesicles derived from these cells. Importantly, TF mediated activation of coagulation is critically important for arterial thrombosis in the setting of atherosclerotic disease. The major endogenous inhibitor of the TF:factor VIIa complex is TF pathway inhibitor 1 (TFPI-1), which is also present in atherosclerotic plaques. In mouse models, increased or decreased expression of TFPI-1 has been found to alter atherosclerosis. This review highlights the contribution of TF-dependent activation of coagulation to atherthrombotic disease. Highlights: Tissue Factor (TF) is highly expressed in human atherosclerotic plaques. TF pathway inhibitor regulates atherosclerotic plaque development. TF driven activation of coagulation is critical for atherothrombosis.